Cerebral vasospasm - Macdonald, R. Loch (Robert Loch) (Academic Press, 2001)
Bryce Weir is a high-profile, respected neurologist. Dr. Macdonald is a colleague of Dr. Weir's and is a "rising star" in the field of neurology. This book is the first to cover all aspects of cerebral vasospasm in depth. It takes the reader from the first descriptions of this puzzling and deadly phenomenon to the latest laboratory evidence explaining its pathophysiology. Packed with clinical pearls, it is a must for neurosurgeons, interventional radiologists, neurologists, and neuropathologists. Key Features * Examines the current understanding of vascular smooth muscle physiology * Provides in-depth overviews of symptoms and treatments * Written by acknowledged experts on the subject * Vividly illustrated with beautiful photographs and diagrams * Cites over 4,000 key papers on vasospasms * Presents key data in an easy-to-use format